2021
DOI: 10.5194/gmd-2021-179
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A simple and efficient model for orographic precipitation

Abstract: Abstract. The influence of climate on landform evolution has received great interest over the past decades. While many studies aim at determining erosion rates or parameters of erosion models, feedbacks between tectonics, climate and landform evolution have been discussed, but addressed quantitatively only in a few modeling studies. One of the problems in this field is that coupling a large-scale landform evolution model with a general circulation model would dramatically increase the theoretical and numerical… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…During the summer, heating of the atmosphere in the south of the CH (Terai) region amplifies atmospheric instability due to orographic lifting, resulting in deep convective events in that region [34]. Previous studies using the orographic moisture flux (OMF) and evapotranspiration showed that orographic lifting influences precipitation significantly [3,41,42]. Trapero et al (2013) argued that the OMF values were high in a conditionally unstable environment (high CAPE) [42].…”
Section: Resultsmentioning
confidence: 99%
“…During the summer, heating of the atmosphere in the south of the CH (Terai) region amplifies atmospheric instability due to orographic lifting, resulting in deep convective events in that region [34]. Previous studies using the orographic moisture flux (OMF) and evapotranspiration showed that orographic lifting influences precipitation significantly [3,41,42]. Trapero et al (2013) argued that the OMF values were high in a conditionally unstable environment (high CAPE) [42].…”
Section: Resultsmentioning
confidence: 99%
“…Code and data availability. All codes are available in a Zenodo repository at https://doi.org/10.5281/zenodo.10473156 (Hergarten, 2024b). This repository also contains the data obtained from the numerical simulations.…”
Section: Discussionmentioning
confidence: 99%
“…The open-source landform evolution model OpenLEM (http://hergarten.at/openlem) is employed for all numerical simulations. Since focus is on a minimum scenario, none of the components of OpenLEM beyond fluvial erosion and sediment transport, such as lithospheric flexure and orographic precipitation (Hergarten and Robl, 2021), are used. The fluvial model implemented in OpenLEM is presumably the simplest model of large-scale fluvial erosion and sediment transport.…”
Section: Introductionmentioning
confidence: 99%